Association Between Pitch Break on the 4-Seam Fastball and Slider and Shoulder Injury in Major League Baseball Pitchers: A Case-Control Study. Issue 10 (11th October 2021) - Platt, Brooks N.; Zacharias, Anthony V.; Conley, Caitlin; Hockensmith, Lindsay; Stockwell, Nicholas; Sciascia, Aaron; Stone, Austin V.
Background: Few specific risk factors are known for shoulder injury in professional pitchers. New pitch-tracking data allow for risk stratification based on advanced metrics. Purpose/Hypothesis: The purpose of this study was to determine the association between shoulder injury, pitch frequency, and pitch metrics (velocity, total break, break angle, and spin rate) for the 4-seam fastball, curveball, and slider. We hypothesized that more frequent use of the 4-seam fastball would be associated with shoulder injury. Study Design: Case-control study; Level of evidence, 3. Methods: The Major League Baseball (MLB) database was queried for pitchers who had been placed on the injury list (IL) with a shoulder injury between 2015 and 2019. Injured pitchers were matched 1:1 with controls (pitchers not on the IL with a shoulder injury during the study period), based on age (±1 year), history of ulnar collateral ligament reconstruction, position (starter vs reliever), and pitches thrown during the injury season (±500). Pitch frequency, velocity, horizontal break, vertical break, total break, and spin rate for the season were collected from the Baseball Savant website for the 4-seam fastball, curveball, and slider. Univariate analysis was used to determine group differences for individual variables. Multiple logistic regression was performed to determine odds ratios (ORs) for shoulder injury associated with pitch frequency, velocity, total break, break angle, and spin rate. Covariates included age, position, ulnar collateral ligament reconstruction status, expected weighted on-base average, and total pitches thrown. Results: Overall, 233 injured pitchers were evaluated. The most common reason for IL placement was inflammation (78/233; 33.5%) followed by strain or sprain (61/233; 26.2%). Increased total pitch break was associated with an increased risk of shoulder injury for the 4-seam fastball (OR, 1.340 [95% confidence interval (CI), 1.199-1.509]; P < .001) and slider (OR, 1.360 [95% CI, 1.206-1.554]; P < .001). For the slider, a decreased spin rate (OR = 0.998 [95% CI, 0.997-0.999]; P = .026) and a more vertical break angle (OR = 1.170 [95% CI: 1.073-1.278]; P = .004) were associated with increased risk of injury. Conclusion: Increased pitch break of the 4-seam fastball and slider was associated positively with shoulder injury in MLB pitchers. These findings add to the understanding of throwing injury and ability to detect risk using ball-tracking technology.